Single crystal growth of apatite-type Al-doped neodymium silicates by the floating zone method - An, Tao (2017)
Lanthanoid silicates (Ln9.33Si6O26) adopt the hexagonal apatite structure and show potential as solid oxide fuel cell (SOFC) electrolytes due to their high oxide ion conductivity at intermediate temperatures (500–700 °C). Ions migrate preferentially along the crystallographic c-axis, and can be improved by introducing lower valent elements at the silicon sites. To better understand this phenomenon, single crystals of aluminium-doped neodymium silicate Nd9.33+x/3AlxSi6−xO26 (0≤x≤1) were synthesised using the floating-zone method in an inert environment at a growth rate of 5 mm/L. The products with x<1.5 were homogeneous, transparent and crack-free crystals. For x=1.5 the monophasic crystal contained minor cracks after cooling and for x=2 a two phase (apatite+NdAlO3) polycrystalline mass was obtained. The quality of the 0≤x≤1.5 crystals were confirmed by neutron diffraction and synchrotron X-ray rocking curve diffraction. The incorporation of aluminium into apatite at nominal concentrations was independently established by energy dispersive X-ray spectroscopy (EDX), and electron backscatter diffraction (EBSD) found the crystallographic habit showed extension along [001].